Introducing MOOC-like methodologies in a face-to-face undergraduate course: a detailed case study. Issue 1 (2nd January 2019) - Brita-Paja, J. L.; Gregorio, C.; Llana, L.; Pareja, C.; Riesco, A.
ABSTRACT: During the last years online education, in particular Massive Open Online Courses (MOOCs), has contributed to spread and popularize educational methodologies such as peer-review, automatic assessment, self-paced courses, self-evaluation, etc. Although these techniques can benefit face-to-face courses, most of them are not yet widely used in these courses. In this paper we present our experience integrating MOOC-like techniques in a face-to-face first year undergraduate course. We describe the academic and institutional context of the project, how we designed and adapted the methodologies to our face-to-face course, the software tools that we have used and developed to support and integrate such methodologies and, finally, we discuss some lessons learned from the experience that can be useful to potential users of these methodologies in face-to-face courses.